Implementación de un sistema para el control del inventario, aplicando el proceso de software personal (psp), para la empresa SOBUAD CÍA. LTDA., ubicada en la provincia de Cotopaxi, cantón Latacunga - Tapia Pérez, Sandra Patricia (2013)
Inventory systems have now become a way of life since there are no barriers to carry out transactions of both purchases and sales of items that can help users to facilitate their way of life. Companies in general invest large amounts of money in automating this sector of the company since they are the core of any company or institution, which generates is that they are aware of how much they have in the assets of a company. As a company dedicated to the trade in technology and household appliances, Sobuad Cia. Ltda. Has believed it advisable to improve this service with a system that helps to better manage its inventories as this will allow its warehouses to be well equipped and prevent Its clients look at business alternatives abroad mainly since, according to the latest surveys, it has been verified that all look at alternatives to import electronic equipment from Europe or the United States, and at the same time also compete with large multinational companies based in the city of Latacunga.